Implementation of Fuzzy Logic to Automatic Flower Irrigation Device Using Matlab - Raihan, Ismi; Daud, Muhammad; Hasibuan, Arnawan; Mardhiah, Ainal; Kerimzade, Gulschen (LPPM Universitas Andalas, 2024)
Fuzzy logic is a logic that has values of fuzziness or ambiguity between true and false. Values in fuzzy logic typically range from 0 to 1. The theory of fuzzy logic is widely used for control systems in various fields. An automatic flower irrigation system is an automated watering device that can be operated with fuzzy logic. In this research, there are two main parameters: temperature and humidity. For the temperature parameter, five linguistic variables are used: cold, cool, normal, warm, and hot. Meanwhile, for soil moisture, three linguistic variables are used: dry, moist, and wet. The results of this research are the maximum setting points obtained according to the rules that have been defined. In this study, the maximum setting point is achieved with a high temperature and low humidity. The difference in output between the Mamdani and Sugeno methods is not very significant. The Mamdani method produces real number values, while the Sugeno method produces integer values. This difference is due to several factors, one of which is the difference in the use of formulas in the defuzzification process of each method.